Testing the Credibility of Belgium's Exchange Rate Policy - Halikias, Ioannis (Washington, D.C. : International Monetary Fund, 1993)
This paper examines the credibility of the exchange rate policy pursued by the Belgian monetary authorities of pegging the Belgian franc to a narrow fluctuation band around the deutsche mark, in the context of the exchange rate mechanism of the European Monetary System. Simple interest rate corridor analysis, based on the Belgian-German long-term interest rate differential and taking explicit account of the currency's position within its fluctuation band, would appear to suggest that the hypothesis that long-run exchange rate credibility has been attained should be rejected, even though considerable progress has been made in this regard since the early 1980s. The paper proceeds to decompose the Belgian-German interest rate differential into a sovereign credit risk and an exchange rate risk component, via the modelling of inflationary expectations, and concludes that long-run exchange rate credibility cannot be rejected from 1990 onwards.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet